Two-factor wearable device authentication protocol based on PUF and IPI - Jun WANG; Shu-bo LIU; Cai LIANG; Yong-kai LI (Tongxin xuebao)
Wearable device is pushing the rapid development of mobile health,however,the open architecture of wireless body area network has brought challenges for the security of user data.In order to protect the security of user data,a two-factor authentication protocol between device note and data hub was proposed based on physically unclonable function and interpulse interval.Using dual uniqueness of device physical characteristic and user biometric trait,the protocol can resist compromise and impersonation attacks and was specially suitable for resource constrained wearable devices under body area network.Compared with the existing authentication schemes,the security of the proposed protocol was enhanced.The practicability and effectiveness of the protocol are confirmed by hardware implementation on FPGA.